Pengaruh Refillable System dan Kesadaran Ramah Lingkungan terhadap Repeat Purchase Intention pada Konsumen Produk Sabun Cair Nuvo di Jabodetabek - Annisa Rahmawati Fadjrin; Rohani Lestari Napitupulu; Unggul Tri Prakoso; Ari Wardi; Yuni Aulia Fauziah; Alifia Putri Ramadhania (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
This study aims to analyze the influence of refillable systems and environmental awareness on repeat purchase intention among consumers of Nuvo liquid soap products in the Jabodetabek area. The study was motivated by increasing public concern regarding environmental issues and the need for companies to implement sustainable marketing strategies through refillable systems. This research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 respondents who had used Nuvo liquid soap and were familiar with Nuvo refill products. The sampling technique used was purposive sampling, while data were analyzed using multiple linear regression with the assistance of SPSS software. The results showed that the refillable system had a positive and significant effect on repeat purchase intention. These findings indicate that ease of use, cost efficiency, and perceived environmental benefits encourage consumers to repurchase Nuvo liquid soap products. Meanwhile, environmental awareness did not have a significant effect on repeat purchase intention, suggesting that repurchase decisions are influenced more by direct product benefits than by environmental considerations. However, refillable systems and environmental awareness simultaneously had a significant effect on repeat purchase intention. The findings imply that companies should continue developing refillable programs that are accessible, economical, and capable of providing added value to consumers as part of sustainable marketing strategies. Such efforts may enhance customer loyalty while supporting plastic waste reduction. Furthermore, this study may serve as a reference for future research on consumer behavior toward environmentally friendly products and sustainable consumption practices in Indonesia generally.